PENDIDIKAN TANPA KEKERASAN: TELAAH PENDIDIKAN RAMAH ANAK DALAM KISAH LUQMAN AYAT 13-19 - dan Afifah Ramdani, Kamridah Karmawati (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2024)
Violence against children still often occurs in educational institutions. In fact, the Koran provides guidance on the concept of child-friendly education, as in Luqman's story. This research aims to explore the concept of child-friendly education in Surah Luqman verses 13-19. Research library research method with a thematic and hermeneutic approach. The results show that Luqman's education includes: 1) gentle advice methods; 2) exemplary; 3) dialogue; 4) habituation to noble morals; and 5) telling stories. Implementation includes: speaking gently, giving an example, patiently educating, following the child's understanding, and not being a burden. In conclusion, the educational concept in Luqman's story is relevant to be applied to create child-friendly education in Indonesia.